Identification of Large Japanese field mouse Apodemus speciosus food plant resources in an industrial green space using DNA metabarcoding - Taichi Fujii; Hirokazu Kawamoto; Tomoyasu Shirako; Masatoshi Nakamura; Motoyasu Minami (PLoS ONE, 2025)
DNA metabarcoding was employed to identify the food plant resources of the Large Japanese field mouse Apodemus speciosus inhabiting an artificial green space on reclaimed land on the Chita Peninsula in Aichi Prefecture, Central Japan, from 2012 to 2014. DNA metabarcoding was performed using high-throughput sequencing of partial rbcL sequences extracted from fecal samples collected in the study area. The obtained sequences, which were analyzed using a constructed local database, revealed that a total of 72 plant taxa were utilized as food plant resources by A. speciosus. Of these plant taxa, 43 could be assigned to species (59.7%), 16 to genus (22.2%), and 13 to family (18.1%). Of the 72 plant taxa identified in this study, the dominant families throughout all collection periods were Lauraceae (81.0% of 100 fecal samples), followed by Fagaceae (70.0%), Rosaceae (68.0%), and Oleaceae (48.0%). Fifty of the 72 plant taxa identified as food plant resources were woody plants. The findings showed that DNA metabarcoding using a local database constructed from the National Center for Biotechnology Information (NCBI) database and field surveys was effective for identifying the dominant food plants in the diet of A. speciosus. The results of this study provided basic information that can be applied to the formulation and implementation of management and conservation strategies for local wildlife.